The Prognostic Significance of ZNF384 Fusions in Adult Ph-Negative B-Cell Precursor Acute Lymphoblastic Leukemia: A Comprehensive Cohort Study From a Single Chinese Center - Qin, Ya-Zhen; Jiang, Qian; Xu, Lan-Ping; Wang, Yu; Jiang, Hao; Dao, Feng-Ting; Chen, Wen-Min; Zhao, Xiao-Su; Liu, Yan-Rong; Zhang, Xiao-Hui; Liu, Kai-Yan; Huang, Xiao-Jun (Frontiers in Oncology, 2021)
Novel recurrent fusion gene types such as zinc finger protein 384 (ZNF384) fusions have been identified in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) with the application of next-generation sequencing technologies. However, the comprehensive large-scale clinical cohort study for clarifying their prognostic significance remains scarce to date. A total of 242 consecutive adult Ph-negative BCP-ALL patients treated in our institute were retrospectively screened ZNF384 fusions at diagnosis by multiplex real time quantitative PCR. ZNF384 fusions were identified in 47 patients (19.4%) and all belonged to B-other ALL (having no high hyperdiploid karyotype, BCR-ABL1, TCF3-PBX1, ETV6-RUNX1 or MLL rearrangement). In the whole cohort, patients with ZNF384 fusions had significantly higher 3-year relapse-free-survival (RFS) and tended to have a higher 3-year overall survival (OS) than those with no ZNF384 fusions (80.1% vs 52.5%, P = 0.013; 67.6% vs 54.0%, P = 0.10). For both patients receiving chemotherapy alone and when patients who received allogeneic-hematologic stem cell transplantation (allo-HSCT) were censored at the time of transplantation, patients with ZNF384 fusions had both similar RFS and similar OS to B-other ALL patients with no ZNF384 fusions (RFS: P =0.94 and 0.30; OS: P =0.94 and 0.51). For patients receiving transplantation, those with ZNF384 fusions had significantly higher 3-year RFS than B-other ALL patients with no ZNF384 fusions and their OS were similar (P = 0.022 and 0.24). Only 2 of 31 patients with ZNF384 fusions and receiving allo-HSCT relapsed, which individually occurred at 66.8 and 69.8 months after transplantation. Therefore, ZNF384 fusion is common in adult BCP-ALL, which may define a new group from BCP-ALL containing no classical fusion transcript with better prognosis through receiving allo-HSCT.